Parallels in autocracy : how nations lose their liberty - Mack, Wolfgang (Wamfam Press, 2022)
Drawing from personal experience as a German child growing up during the rise of Hitler, and later living in other countries whose democracies slid into autocracy in similar ways, Mack's Parallels in Autocracy is compellingly insightful and deeply chilling. Reflecting on our species' self-destructive tendency to relinquish freedom to autocrats, the author finds not only tragedy, but also compassion for the human condition and hope